Sibling split Party of nine - Higgins, M G; Taylor, Jo (North Mankato, Minnesota Stone Arch Books, a Capstone imprint, 2017)
It is the first Thanksgiving since their parents split up, and twelve-year-old Arnie has come to the farm to spend the weekend with eleven-year-old Annabelle and their father at the farm--and when it starts to looks like it will just be the three of them, Arnie and Annabelle decide to invite several of their neighbors over for the feast
A gift from book Africa
English stories
soft copy
1 2 13
NEW_ZTN_GN
Keywords: Children of separated parents -- Juvenile fiction; Thanksgiving Day -- Juvenile fiction